UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK MENGGUNAKAN METODE TANYA JAWAB TEMA 1 INDAHNYA KEBERSAMAAN BUDAYA BANGSAKU KELAS IV SD NEGERI 101798 DELI TUA - Salsabila Putri Wijaya; Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' listening skills through a question and answer method that involves active interaction between teachers and students. Lack of listening skills in students requires a focused and structured approach so that listening skills can develop gradually. Listening is understood as a means to understand the meaning of language sounds, which requires discipline, concentration, active participation, and understanding and assessment. Through the question and answer method, students are expected to be able to improve their responses to questions and improve their understanding of the material presented. With optimal listening skills, students will gain new knowledge and insights that can support the development of their potential. This study is expected to contribute to improving the quality of learning through improving listening skills in elementary schools.